Four-Strand Hamstring Autografts Less Than 8-mm Wide Provide Less Capability for Conversion to a 6- or 7-Strand Graft Than Larger-Diameter Hamstring Autografts - W.P. Yau, M.B.B.S., F.R.C.S.Ed., F.H.K.C.O.S., F.H.K.A.M. (Orthopaedic Surgery) (Arthroscopy, Sports Medicine, and Rehabilitation, 2025)
Purpose: To report the proportion of patients who have long-enough hamstring (HS) tendons to prepare an anterior cruciate ligament reconstruction (ACLR) graft of 5 strands, 6 strands, 7 strands, or 8 strands in patients with a small 4-strand HS ACLR graft diameter <8 mm (HS-ACLR-4S <8 mm) compared with patients who had a 4-strand HS ACLR graft diameter ≥8 mm (HS-ACLR-4S ≥8 mm). Methods: Patients who underwent medial HS harvest for single-bundle ACLR between 2008 and 2018 were included. Patients were included if the ACLR graft was a doubled semitendinosus and doubled gracilis autograft and they were skeletally mature. The primary outcome was the length of the HS. The likelihood of successful preparing an HS ACLR with 5 strands of tendons or more (HS-ACLR ≥5S) was compared between HS-ACLR-4S <8 mm and HS-ACLR-4S ≥8 mm. Any anthropometric factors significantly associated with the feasibility of preparing a HS-ACLR≥5S were reported. Results: A total of 296 patients, including 223 men and 73 women, were included. One hundred patients had HS-ACLR-4S <8 mm, whereas 196 patients had HS-ACLR-4S ≥8 mm. The length of the HS was shorter in the HS-ACLR-4S <8-mm group compared with the HS-ACLR-4S ≥8-mm group (P < .001). There was no significant difference between the 2 groups in the chance of successfully preparing a 5-strand graft (97% and 98%, respectively; P = .327). However, there was a lower chance of preparing an ACLR graft using 6 or 7 strands of tendons in patients with HS-ACLR-4S <8-mm (P = .031 and P < .001, respectively). In addition, body height was the sole independent predictor of the likelihood of successfully preparing a HS-ACLR of more than 5 strands of tendon. Conclusions: Preparation of a 5-strand ACLR graft is almost always possible, regardless of whether the HS-ACLR-4S graft diameter was less than 8 mm or 8 mm or greater. Shorter body height was associated with a lower chance of successfully preparing an HS-ACLR with 5 strands of tendons. However, the likelihood of successfully preparing a 6-strand and a 7-strand HS-ACLR graft were lower in the group of patients with an HS-ACLR-4S <8 mm compared with HS-ACLR-4S ≥8 mm. Clinical Relevance: Understanding the factors related to ACL HS tendon autograft preparation can allow surgeons to ensure grafts of adequate length and diameter.